Sustainable Development and Landscape Protection in Low-Income Urban Coastal Areas: Empowerment Through Sovereignty and Deliberative Participation - Meilasari-Sugiana, Astrid; Madonna, Sandra; Putri, Dianingtyas; Solikhah, Solikhah (Disease Prevention and Public Health Journal, 2021)
Background: The Government of Indonesia is currently implementing its Coastal Community Economic Empowerment Program or Pemberdayaan Ekonomi Masyarakat Pesisir (PEMP) to numerous coastal communities in the island of Java, Sumatra, Sulawesi, Kalimantan and Nusa Tenggara. The program is geared to empower local coastal communities through its integrated, holistic vision, its local-based, participatory method, and its public-partnership approach. Locality is important since the program aims to induce local initiatives and retain social and economic progress within the area, taking into account its ecological carrying capacity. Method: The research is a qualitative inquiry using ethnomethodological tools and purposive, snowball sampling. The research was conducted in 2015-2016 in Cilacap, Central Java.   Data analysis was conducted through tabulation, categorization, comparison, conceptualization and theorization. Results: Issues beset the government’s PEMP program, including its utilitarian framework to coastal resource governance, its adverse incorporation of small fishermen into the fishing industries, and its unsustainable public-private partnership to promote entrepreneurial growth. Attempts to resolve those issues include ensuring that funding for the PEMP program is incorporated within the yearly provincial and regency budgets and regulations, instilling consensus building over the program’s direction and activities with local communities and the private sector through the Provincial and Regency Level People’s Representative Council, and brokering with local communities and the private sector to achieve workable common ground should conflicts arise. Conclusion: Establishing sound intervention policies and programs require securing flexibility and adaptive management capacity through negotiations and brokering.